2015
DOI: 10.1016/j.annemergmed.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasonography by Pediatric Emergency Physicians

Abstract: Point-of-care ultrasonography is increasingly being used to facilitate accurate and timely diagnoses and to guide procedures. It is important for pediatric emergency physicians caring for patients in the emergency department to receive adequate and continued point-of-care ultrasonography training for those indications used in their practice setting. Emergency departments should have credentialing and quality assurance programs. Pediatric emergency medicine fellowships should provide appropriate training to phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 104 publications
0
50
0
Order By: Relevance
“…PEM practitioners reported having difficulty learning PEM POCUS through informal, self‐directed learning programs due to competing demands for their time. POCUS is a complex and highly technical imaging modality that involves both cognitive and psychomotor skill sets . Accordingly, developing PEM POCUS skills requires substantial formal education programs with dedicated time to learn and practice, as well as the provision of assessment and feedback to the learner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEM practitioners reported having difficulty learning PEM POCUS through informal, self‐directed learning programs due to competing demands for their time. POCUS is a complex and highly technical imaging modality that involves both cognitive and psychomotor skill sets . Accordingly, developing PEM POCUS skills requires substantial formal education programs with dedicated time to learn and practice, as well as the provision of assessment and feedback to the learner.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, POCUS has gained recognition in the field of pediatric emergency medicine (PEM) as an ideal imaging modality as it is painless, noninvasive, rapid, and dynamic . Most importantly, ultrasound does not use ionizing radiation, which has the potential for harmful effects over the course of a lifetime .…”
Section: Milestones Utilized For Measuring Physician Competencymentioning
confidence: 99%
See 1 more Smart Citation
“…For this initial effort, we assembled members of a pediatric emergency POCUS work group, which wrote the recently published POCUS guidelines for pediatric emergency physicians [13, 14]. With collaboration from additional content experts in the field, who had either completed an ultrasound fellowship or specialty training in pediatric emergency POCUS, we sought to create a comprehensive document summarizing the current evidence.…”
mentioning
confidence: 99%
“…The American Academy of Pediatrics acknowledged point-of-care sonography use and training in PEM and recently published the first guidelines for pointof-care sonography implementation by PEM physicians in July 2015. 16,17 While comprehensive expertise in the use of point-of-care sonography requires dedicated training often spanning months, recent studies have demonstrated that the use of an objective-driven ultrasound curriculum can be used to effectively train clinicians in clinically relevant pointof-care sonography in a relatively short time. [18][19][20][21] Currently, published guidelines on accreditation of the neonatologist for targeted neonatal echocardiogram exist, 22,23 but these guidelines are cumbersome Figure 5.…”
Section: Lessons Learned-need For Formal Curriculum Credentialing Gumentioning
confidence: 99%